Management of Islamic Boarding School Shapes the Character of Santri Discipline - Berkah, Dian; Zamroni, M. Afif (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
This research aims to describe the implementation of student discipline at the Assyariatul Uluum Islamic Boarding School. This research used qualitative research, and data collection was carried out through interviews, observation, and documentation, all of which were used to answer questions about the management of student discipline at the Assyariatul Uluum Sumedang Islamic Boarding School. Findings in the management of Santri discipline, including Planning for Santri discipline at the Assyariatul Uluum Sumedang Islamic Boarding School, including a) formulating Santri discipline goals by the vision, mission, and objectives of the Assyariatul Uluum Sumedang Islamic Boarding School; b) make disciplinary regulations for students; c) create guidelines for violations along with sanctions that will be given to disciplinary violators; and d) determine a schedule of student disciplinary activities. The implementation of Santri discipline at the Assyariatul Uluum Islamic Boarding School includes: 1) Providing direction regarding Santri discipline. 2) Motivate students regarding student discipline. 3) Lead the course of student discipline. 4) Communicate with students to provide an understanding of student discipline. 5) Make decisions regarding student disciplinary violations.